TECHNOLOGICAL INNOVATIONS IN ORDER PROCESSING AND THEIR IMPACT ON LOGISTICS IN THE NIGERIAN CONSTRUCTION INDUSTRY - Bello , Aminu Olatunde (Ayden International Journal of Banking, Finance and Technology, 2025)
The logistic technologies for effective and efficient ‘order processing operations’ in the areas of tracking, shipping, replenishment, dispatching and holding of inventory are deficient in the Nigerian construction industry, when compared to manufacturing and retailing sectors. This is confirmed to have a significant effect on the performance of the construction sector. This article assessed how order processing technology utilised by manufacturing and retail industries could improve the order processing logistics operations of the construction industry. Lagos State and the F.C.T. Abuja, Nigeria, were the selected geographical study areas, from which five manufacturing companies, five retailing companies and five construction projects were purposively selected. Processing technology in the logistics system could lead to full efficiency gains in the order processing aspect of the construction industry. It is recommended that the Federal Government of Nigeria should mandate all major construction project stakeholders to attend workshops on the use of recent technologies in the management of construction operations.